Molecular Dynamics Simulations Suggest Ligand’s Binding to Nicotinamidase/Pyrazinamidase - Zhang, Ji-Long; Zheng, Qing-Chuan; Li, Zheng-Qiang; Zhang, Hong-Xing (PLOS ONE, 2012)
The research on the binding process of ligand to pyrazinamidase (PncA) is crucial for elucidating the inherent relationship between resistance of Mycobacterium tuberculosis and PncA’s activity. In the present study, molecular dynamics (MD) simulation methods were performed to investigate the unbinding process of nicotinamide (NAM) from two PncA enzymes, which is the reverse of the corresponding binding process. The calculated potential of mean force (PMF) based on the steered molecular dynamics (SMD) simulations sheds light on an optimal binding/unbinding pathway of the ligand. The comparative analyses between two PncAs clearly exhibit the consistency of the binding/unbinding pathway in the two enzymes, implying the universality of the pathway in all kinds of PncAs. Several important residues dominating the pathway were also determined by the calculation of interaction energies. The structural change of the proteins induced by NAM’s unbinding or binding shows the great extent interior motion in some homologous region adjacent to the active sites of the two PncAs. The structure comparison substantiates that this region should be very important for the ligand’s binding in all PncAs. Additionally, MD simulations also show that the coordination position of the ligand is displaced by one water molecule in the unliganded enzymes. These results could provide the more penetrating understanding of drug resistance of M. tuberculosis and be helpful for the development of new antituberculosis drugs.